Nucleoside Metabolism Is Induced in Common Bean During Early Seedling Development - Delgado-García, Elena; Piedras, Pedro; Gómez-Baena, Guadalupe; García-Magdaleno, Isabel M.; Pineda, Manuel; Gálvez-Valdivieso, Gregorio (Frontiers in Plant Science, 2021)
Nucleoside hydrolases (nucleosidases) catalyze the cleavage of nucleosides into ribose and free nucleobases. These enzymes have been postulated as key elements controlling the ratio between nucleotide salvage and degradation. Moreover, they play a pivotal role in ureidic legumes by providing the substrate for the synthesis of ureides. Furthermore, nucleotide metabolism has a crucial role during germination and early seedling development, since the developing seedlings require high amount of nucleotide simultaneously to the mobilization of nutrient in cotyledons. In this study, we have cloned two nucleosidases genes from Phaseolus vulgaris, PvNSH1 and PvNSH2, expressed them as recombinant proteins, and characterized their catalytic activities. Both enzymes showed a broad range of substrate affinity; however, PvNSH1 exhibited the highest activity with uridine, followed by xanthosine, whereas PvNSH2 hydrolyses preferentially xanthosine and shows low activity with uridine. The study of the regulation of nucleosidases during germination and early postgerminative development indicated that nucleosidases are induced in cotyledons and embryonic axes just after the radicle emergence, coincident with the induction of nucleases activity and the synthesis of ureides in the embryonic axes, with no remarkable differences in the level of expression of both nucleosidase genes. In addition, nucleosides and nucleobase levels were determined as well in cotyledons and embryonic axes. Our results suggest that PvNSH1 and PvNSH2 play an important role in the mobilization of nutrients during this crucial stage of plant development.